Embedding Green Values: The Role of Organizational Culture in Advancing HRM Driven Sustainability in Healthcare - B. Dilip; Ragini (Sustainable Development, 2026)
ABSTRACT This research explores how green organizational culture (GOC) influences the relationship between green human resource management (GHRM) practices and environmental performance (EP) in the healthcare sector. The study used a mixed‐methods approach by collecting qualitative data in the form of semi‐structured interviews with 10 healthcare professionals, alongside quantitative data from surveys completed by 217 hospital staff members in Vellore, India. The findings reveal a strong positive direct relationship between green human resource management practices and environmental performance. Additionally, the results show that green organizational culture acts as a partial mediator on this relationship, suggesting that embedding green values and cultural norms within hospital environments can significantly improve environmental outcomes. By combining qualitative perspectives with quantitative analysis, this study provides a thorough understanding of how GHRM efforts support sustainability goals in healthcare organizations. The conclusions highlight the significance of cultivating an environmentally conscious organizational culture to enhance the success of environmental initiatives. Although this study is limited to professional staff, future work may encompass non‐professional employees to capture a more holistic view of environmental engagement throughout hospital operations.